Schistosomiasis is associated with rectal mucosal inflammation among Kenyan men who have sex with men. (July 2021) - Mehta, Supriya D; Okal, Duncan; Otieno, Fredrick; Green, Stefan J; Nordgren, Rachel K; Huibner, Sanja; Bailey, Robert C; Bhaumik, Dulal K; Landay, Alan; Kaul, Rupert
Background: Schistosoma mansoni infection is hyperendemic in Lake Victoria communities and associated with cervicovaginal immune alterations and HIV acquisition. We assessed the hypothesis that schistosomiasis correlates with greater rectal inflammation in men who have sex with men (MSM) in Kisumu, Kenya.Methods: In this cross-sectional study of 38 HIV-negative MSM aged 18–35 years, schistosomiasis was diagnosed by urine circulating cathodic antigen (CCA). Microbiome was assessed in rectal swabs by 16S rRNA gene amplicon sequencing, and rectal inflammation by quartile normalized summative score of inflammatory cytokines (IL-1α, IL-1β, IL-8, and TNF-α). Elastic net (EN) regression identified taxa associated with inflammation. Multivariable linear regression estimated the association between inflammation score and schistosomiasis and bacteria identified in EN.Results: Most men were CCA positive (24/38; 63%), and median rectal inflammation score was significantly higher in these participants (11 vs. 8, p = 0.04). In multivariable regression, CCA-positive men had 2.85-point greater inflammation score ( p = 0.009). The relative abundance of Succinivibrio (coefficient = −1.13, p = 0.002) and Pseudomonas (coefficient = −1.04, p = 0.001) were negatively associated with inflammation.Discussion: CCA positivity was associated with rectal mucosal inflammation, controlling for rectal microbiome composition. Given its high prevalence and contribution to inflammation, schistosomiasis may have important implications for HIV transmission in this vulnerable population.